Central nervous system complications after liver transplantation. Issue 8 (August 2015) - Kim, Jeong-Min; Jung, Keun-Hwa; Lee, Soon-Tae; Chu, Kon; Roh, Jae-Kyu
Abstract We investigated the diversity of central nervous system complications after liver transplantation in terms of clinical manifestations and temporal course. Liver transplantation is a lifesaving option for end stage liver disease patients but post-transplantation neurologic complications can hamper recovery. Between 1 January 2001 and 31 December 2010, patients who had undergone liver transplantation at a single tertiary university hospital were included. We reviewed their medical records and brain imaging data and classified central nervous system complications into four categories including vascular, metabolic, infectious and neoplastic. The onset of central nervous system complications was grouped into five post-transplantation intervals including acute (within 1 month), early subacute (1–3 months), late subacute (3–12 months), chronic (1–3 years), and long-term (after 3 years). During follow-up, 65 of 791 patients (8.2%) experienced central nervous system complications, with 30 occurring within 1 month after transplantation. Vascular etiology was the most common (27 patients; 41.5%), followed by metabolic (23; 35.4%), infectious (nine patients; 13.8%), and neoplastic (six patients). Metabolic encephalopathy with altered consciousness was the most common etiology during the acute period, followed by vascular disorders. An initial focal neurologic deficit was detected in vascular and neoplastic complications, whereas metabolic and infectious etiologies presented with non-focal symptoms. Our study shows that the etiology of central nervous system complications after liver transplantation changes over time, and initial symptoms can help to predict etiology.